The mind-gut connection : how the hidden conversation within our bodies impacts our mood, our choices, and our overall health - Mayer, Emeran A. (Harper Wave, an imprint of HarperCollins Publishers, 2018)
While the dialogue between the gut and the brain has been recognized by ancient healing traditions, including Ayurvedic and Chinese medicine, Western medicine has failed to appreciate the complexity of how the brain, gut, and more recently, the microbiome (the microorganisms that live inside us) communicate with one another. Dr. Emeran Mayer offers a revolutionary look at this developing science, teaching us how to harness the power of the mind-gut connection to take charge of our health. The Mind-Gut Connection shows how to keep the brain-gut communication clear and balanced to: heal the gut by focusing on a plant-based diet; balance the microbiome by consuming fermented foods and probiotics, fasting, and cutting out sugar and processed foods; promote weight loss by detoxifying and creating healthy digestion and maximum nutrient absorption; boost immunity and prevent the onset of neurological diseases such as Parkinson's and Alzheimer's; generate a happier mindset and reduce fatigue, moodiness, anxiety, and depression; prevent and heal GI disorders such as leaky gut syndrome, food sensitivities and allergies, and IBS, as well as digestive discomfort such as heartburn and bloating.